Implementasi Program Rumah Kasih Sayang Dalam Pemberdayaan Orang Dengan Kecacatan (Studi di Desa Krebet, Kecamatan Jambon, Kabupaten Ponorogo) - Rakhmawati, Erlin (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of Compassion House Program for The Empowerment the Disabled People (Study at Desa Krebet , Kecamatan Jambon, Kabupaten Ponorogo). Compassion House Program for the empowerment of the disabled people (ODK) is a program from Social Ministry which is aimed to improve the service and empowerment given to the people with social welfare problem, especially the disabled people in Ponorogo, in manner of integration and accomplishment. This program is implemented by Compassion Social Organization which must report to The Official of Social, Workforce and Transmigration of Ponorogo Regency. Compassion Social Organization is the Implementer Team of Compassion House Program which is also submissive to The Official of Social, Workforce and Transmigration of Ponorogo Regency. Research attempts to analyze how is the implementation of Compassion House Program for the empowerment of the disabled people and also to identify the factors supporting and constraining the implementation of Compassion House Program. Research method is qualitative. implementation of Compassion House Program is already good. However, there are also constraining factors such as limited accessibility, lack of funding, fluctuated emotion among the disabled people, and the difficulty of the disabled people to adapt with their environment. Keyword: implementation, Compassion House Program, empowerment, the disabled people Abstrak: Implementasi Program Rumah Kasih Sayang Dalam Pemberdayaan Orang Dengan Kecacatan (Studi di Desa Krebet, Kecamatan Jambon, Kabupaten Ponorogo). Program Rumah Kasih Sayang dalam Pemberdayaan Orang Dengan Kecacatan merupakan sebuah program dari Kementerian Sosial yang bertujuan meningkatkan pelayanan dan pemberdayaan penyandang masalah kesejahteraan sosial khususnya Orang Dengan Kecacatan yang ada di Ponorogo secara terpadu dan tuntas. Program ini berada dibawah naungan Dinas Sosial, Tenaga Kerja dan Transmigrasi Kabupaten Ponorogo. Penelitian ini dimaksudkan untuk menganalisa bagaimana implementasi program Rumah Kasih Sayang serta mengidentifikasi faktor pendukung maupun penghambatnya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Program Rumah Kasih Sayang sampai saat ini sudah berjalan dengan baik. Namun dalam pelaksanaannya masih terdapat beberapa hambatan seperti aksesbilitas, sumber dana, suasana hati, dan adaptasi dengan lingkungan sekitar. Â  Kata kunci: implementasi, Program Rumah Kasih Sayang, pemberdayaan, orang dengan kecacatan.